2015
DOI: 10.1038/srep18384
|View full text |Cite
|
Sign up to set email alerts
|

A white spot syndrome virus microRNA promotes the virus infection by targeting the host STAT

Abstract: JAK/STAT pathway plays an important role in invertebrates during virus infection. However the microRNA (miRNA)-mediated regulation of JAK/STAT is not intensively investigated. Viral miRNAs, encoded by virus genome, have emerged as important regulators in the virus-host interactions. In this study, a WSSV (white spot syndrome virus)-encoded miRNA (WSSV-miR-22) was characterized in shrimp during virus infection. The results showed that the viral miRNA could promote WSSV infection in shrimp by targeting the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…Another key study identified 89 WSSV miR-NAs, from which WSSV-miR-N24 was described as a suppressor of host antiviral apoptosis, by targeting the shrimp caspase 8 gene and further repressing the apoptosis of haemocytes in vivo . Other reports revealed that several miRNAs, such as: WSSV-miR-66, WSSV-miR-68, WSSV-miR-22 and WSSV-miR-N32 also play important roles in viral disease (He et al 2014(He et al , 2017aRen et al 2015). This evidence indicate that miRNAs may be considered as important regulators of shrimp immune response, being part of the interacting network of molecules that defend such marine organism against viral pathogens.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Another key study identified 89 WSSV miR-NAs, from which WSSV-miR-N24 was described as a suppressor of host antiviral apoptosis, by targeting the shrimp caspase 8 gene and further repressing the apoptosis of haemocytes in vivo . Other reports revealed that several miRNAs, such as: WSSV-miR-66, WSSV-miR-68, WSSV-miR-22 and WSSV-miR-N32 also play important roles in viral disease (He et al 2014(He et al , 2017aRen et al 2015). This evidence indicate that miRNAs may be considered as important regulators of shrimp immune response, being part of the interacting network of molecules that defend such marine organism against viral pathogens.…”
Section: Discussionmentioning
confidence: 88%
“…, ; Ren et al . ). This evidence indicate that miRNAs may be considered as important regulators of shrimp immune response, being part of the interacting network of molecules that defend such marine organism against viral pathogens.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous study, the shrimp miRNAs associated with viral infection were explored (16). To reveal the miRNAs simultaneously involved in autophagy and viral infection, the miRNAs associated with autophagy were compared with those related to viral infection.…”
Section: Host Mirnas Involved In Autophagy and Viral Infectionmentioning
confidence: 99%
“…Our studies have revealed that white spot syndrome virus (WSSV) miRNAs and their host shrimp miRNAs are involved in viral infection (12)(13)(14)(15)(16). Viral miRNAs, such as WSSV-miR-66, WSSV-miR-68, WSSV-miR-N24, and WSSV-miR-22, play very important roles in viral infection (13)(14)(15)(16), whereas shrimp miRNAs, for example, miR-7, -100, and -1000, are necessary for host antiviral immunity and have an important influence on virus invasion (17)(18)(19)(20)(21). The present study showed that the shrimp miRNAs miR-71 and -13b, which were conserved in animals, could simultaneously regulate shrimp autophagy and WSSV infection, connecting host autophagy with viral infection.…”
mentioning
confidence: 99%
“…WSSV-miR-N24 targets the shrimp caspase 8 gene and represses the shrimp apoptosis activity ( 16 ). Meanwhile, although WSSV uses the host defense gene STAT to promote the expression of IE1 ( 17 ), these is also evidence that WSSV-miR-22 benefits the virus by targeting and downregulating the host STAT gene ( 18 ).…”
Section: Introductionmentioning
confidence: 99%